2021
DOI: 10.1080/0020174x.2021.1958054
|View full text |Cite
|
Sign up to set email alerts
|

Predicate order and coherence in copredication

Abstract: This article proposes that predicate order and coherence relations are the two major determining factors in copredication licensing, resolving a long-standing puzzle over the criteria for constructing acceptable copredications. The effects of predicate ordering are claimed to be anchored around semantic complexity, such that copredications with semantically Simple-Complex predicate orderings are more acceptable than the reverse. This motivates a parsing bias, termed Incremental Semantic Complexity. Particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…An explanation of the differences in intuition that our model captures likely boils down to differences in experience, for example, exposure to this or similar sentences. Murphy (2021aMurphy ( , 2021b) suggested that we can explain this asymmetry by parsing preferences: We prefer to process first simpler and then more complex semantic structures. 18 This suggestion is prima facie quite plausible (not least because it follows some commonsense principle of "incremental effort").…”
Section: Context-dependency Of Felicitousnessmentioning
confidence: 99%
See 2 more Smart Citations
“…An explanation of the differences in intuition that our model captures likely boils down to differences in experience, for example, exposure to this or similar sentences. Murphy (2021aMurphy ( , 2021b) suggested that we can explain this asymmetry by parsing preferences: We prefer to process first simpler and then more complex semantic structures. 18 This suggestion is prima facie quite plausible (not least because it follows some commonsense principle of "incremental effort").…”
Section: Context-dependency Of Felicitousnessmentioning
confidence: 99%
“…Finally, for another illustration of how package‐external priors can influence felicitousness judgments, consider so‐called “predicate order effects” in copredication (e.g., Murphy, 2021a , 2021b ; Ortega Andrés, 2020 ; Ortega Andrés & Vicente, 2019 ). Such order effects involve two statements with the same predications (and hence associated senses of the nominal) but in inverted orders.…”
Section: A Pp Approach To Copredicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating order effects in our co-predication samples revealed that only 1 of 229 pairwise comparisons between the acceptability scores of copredication structures with different predicate orderings passed the Bonferroni corrected significance level of 0.00021. We therefore argue that our samples are free from any secondary acceptability factors based on predication order (Murphy, 2021), and therefore indeed primarily test for the acceptability of invoking different senses of the target words. Based on this observation, we again combine results before further analysis.…”
Section: Co-predication Acceptability Ratingsmentioning
confidence: 99%
“…All of these effects are clearly present in a particular instantiation of polysemy known as copredication , whereby multiple, semantically different sense types are associated with a single nominal (“Lunch was delicious but was delayed”; “The newspaper that I held this morning has been sued”). Progressing on from recent research into the acceptability dynamics of copredication ( Murphy, 2019 , 2021a , b ) and possible lower-level accounts ( Murphy, 2018 , 2020 ), I will investigate what I will term the persistence conditions of copredication, making close contact with the nature of prototypical copredications. The main research question addressed will be: What are the conditions under which the identity of a given entity can survive?…”
Section: Introductionmentioning
confidence: 99%